One China, Freely and Fairly Elected: A New Solution to the Issue of Taiwan - Wen, Jean (Columbia Journal of Asian Law, 2007)
On January 1, 2007, President Chen Shui-bian of Taiwan announced in his New Year Message, “The international community must forthrightly pay heed to the will of Taiwan’s people, and must respect their right of free choice.. .The sovereignty of Taiwan belongs to its 23 million people, not to the People’s Republic of China. Only the people of Taiwan have the right to decide Taiwan’s future.”‘ Predictably, the government of the People’s Republic of China (PRC) reacted angrily. The People’s Daily reported that an unnamed spokesman from Beijing’s Taiwan Affairs Office stated that China would never allow Taiwan to formally break away from the Mainland.2 On March 15, 2007, the Chinese People’s Political Consultative Conference, China’s top legislative advisory committee, adopted a resolution that stated, “We shall firmly oppose the secessionist activities in any form to seek the de jure independence of Taiwan.”3 In the case of an armed conflict, the PRC’s obligations under international law will depend on Taiwan’s status as a state. This paper will first briefly discuss the history of Taiwan, and its political development since the Kuomintang’s (KMT)4 loss of the civil war on Mainland China in 1949 to Taiwan’s current democracy. It will proceed with an examination of Taiwan’s status as a state and the implications of this status. Next this note will discuss the PRC’s violations of international law regarding the use of force and human rights with respect to Taiwan. Next, the PRC’s obligations under international law will be addressed, along with suggested responses by the international community in the event of an armed attack. Finally, this paper will assert a new solution to the Taiwan issue: internationally monitored free and fair elections. The status of Taiwan continues to become more precarious. In a 2000 opinion poll on national identity in Taiwan, 36.9% of respondents stated that they considered themselves Taiwanese, 13.1% Chinese, and 43.8% of respondents considered themselves both Taiwanese and Chinese.5 By 2006, in a survey published by the Election Study Center of National Chengchi University, 60.1 % of respondents identified themselves as Taiwanese, only 4.8 % identified themselves as Chinese, and 33.4% identified themselves as both Taiwanese and Chinese.6 With the Taiwanese leadership’s increased push towards formally proclaiming independence and PRC opposition to independence for Taiwan, any military conflict involving China will most likely be over Taiwan. 7 Several key factors underlie the PRC’s continued agitation over Taiwan and its increasingly adamant opposition to Taiwan independence: the PRC does not wish to appear internally weak on Taiwan issues; the PRC considers the international community’s acceptance of its “one-China” policy as an issue of legitimacy and respect; China’s historical legacy; and Taiwan’s strategic military position along with the PRC’s military aspirations.8 How the international community addresses the issue of Taiwan will have an immense impact, not only on the people of Taiwan, but also on global security as a whole.